Syndromic Testing in the Pandemic Era and Beyond: Rapid Detection for Respiratory Infections in Istanbul - Mustafa Onel; Hayriye Kırkoyun Uysal; Arat Hulikyan; Yasemin Ayse Ucar; Gizem Yapar; Aytaj Allahverdiyeva; Serra Zeynep Akkoyunlu; Eray Yurtseven; Mehmet Demirci; Sevim Mese; Ali Agacfidan (Viruses)
The aim of the study was to determine the prevalence rates of respiratory pathogens using syndromic tests and also to show which respiratory viruses were detected in suspected cases, especially during and after the pandemic period. A total of 1984 different respiratory tract samples from various departments were included and studied with the QIAstat-Dx device in 2021–2023. The samples were studied with the QIAstat-Dx1 Respiratory SARS-CoV-2 Panel. The kit used was a fully automated, multiplex syndromic test that detected SARS-CoV-2 and 21 other respiratory tract pathogens. As a result of the study, the prevalence of Rhinovirus/Enterovirus (RV/EV) (18.59%), RV/EV-SARS-CoV-2 (42.74%), SARS-CoV-2 (5.04%), and Influenza A Virus (IAV) (5.59%) agents was found to be higher than other agents during the period investigated. Among the 1984 patients examined, 959 (48.33%) had a single viral agent, 156 (7.86%) had double coinfection, 11 (0.55%) had triple coinfection and 1 patient had quadruple coinfection. Nearly half of the patients had a straightforward infection, which helps clinicians in directing specific treatment methods. The study results demonstrate that during the pandemic period, the detection of respiratory pathogens such as SARS-CoV-2 and RV/EV was not only critical for accurate diagnosis but also served as an important indicator of the broader epidemiological trends in respiratory infections. The seasonal distribution showed that while RV/EV was frequently present, its coinfection with SARS-CoV-2 was notably observed only in the first trimester. In light of our findings showing high rates of SARS-CoV-2 and RV/EV detection, along with diverse patterns of coinfection in clinical samples, such comprehensive testing not only assists in rapid diagnosis but also informs public health strategies by reflecting the evolving landscape of respiratory infections in the pandemic and post-pandemic era.